The Effect of Health Service Quality on The Satisfaction of National Health Insurance Participants at The Internal Medicine Polyclinic of Undata Hospital, Central Sulawesi Province - Risal L, Franciscus Saveris; M, Mustainah; Nawawi, Muhammad (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study analyzed the impact of health service quality on the satisfaction of National Health Insurance (JKN) participants at the Internal Medicine Polyclinic, Undata Hospital, Central Sulawesi. Using explanatory research with purposive sampling, 96 respondents were selected, and data were collected through observation, literature review, and field studies. Analysis included validity, reliability, normality, and regression tests. Results show that dimensions of service quality—responsiveness (2.129), reliability (2.366), assurance (2.151), empathy (2.067), and tangibles (3.795)—significantly influence JKN participant satisfaction. Overall, service quality accounts for 83.2% of patient satisfaction, with 16.8% influenced by other factors.al-Qur’an method, which became a key linguistic approach in Quranic interpretation.